Towards better housing management : service life planning in achieving sustainability for affordable housing - Tapsir, Siti Hamisah; Yatim, J. M.; Usman, F. (2005)
The construction industry has been expected to construct reasonable quality housings that are cheaper, faster to build and most critical to be durable with minimal maintenance required. With the emerging of new technologies and concern for environment, increasing attention in construction industry is given on sustainability. Minimal financial commitment, high standard quality of living and considerations for environment are among the main objectives in assets management. However, anticipated service life of an asset is dependent upon its environment, material properties as well as operations and maintenance. It is generally acknowledged that quality and performance of building components decrease with time and that the imposed loads and the levels of maintenance affect the rate of degradation. However, these issues are normally not being identified earlier during design stage of building construction. By using assessment of building components performance, preventive maintenance, repair and major rehabilitation, decisions can be made based on economic analysis on the life cycle of buildings. Through optimising service life of the building components and its materials, operational and maintenance cost can be reduced. This paper describes a software’s concept, assessment process, data collection and potential applications of development in implementing service life planning for local housing